The characteristic of municipal solid waste from Perlis disposal site - Rohada Saad (School of Environmental Engineering, University Malaysia Perlis, 2013)
In this study, we characterize and determine parameters density, pH, moisture content, calorific value (CV) and heavy metal (Nickel, Zinc, Manganese and Ferum).